PERAN PELAKSANAAN WFH DALAM MENINGKATKAN KINERJA DI MASA PANDEMI (Studi pada ASN Politeknik Penerbangan Surabaya) - Dwi Nur Afifah; Iriani Ismail (Jurnal Kajian Ilmu Manajemen (JKIM), 2022)
The study about the phenomenon during the pandemic, that there is a change in the work system which the work of employees who are usually done in the office can do their work from home (WFH). It means employees no longer need to come the office and face-to-face meetigs with others. Work activities for employees in government agencies are attendance at the office wearing uniforms, and making it with the working hours that have been determined.The aim was to determine the implementation of WFH in improving the employees performance (ASN) at the Surabaya Flight Polytechnic. This type of research uses qualitative research. This study involved 6 people as research subjects or informants. Representative techniques were used in determining the informants in this study. The results indicate that many employees feel uncomfortable with the implementation of WFH, employees performance becomes less than optimal due to limited facilities at home, while obstacles in implementing WFH regarding network constraints are one of the obstacles to WFH implementation. Keywords: WFH, and Performance.